Manajemen Pembelajaran Bahasa Inggris dan Fasilitasi Kegiatan Keagamaan Islam di Lembaga Kursus Central Course Kediri - Fitriani Sopayati; Giyoto Giyoto (Scidac Plus, 2023)
This paper aims to analyze the learning management of English course and facilitate of Islamic activities at Central Course Kediri. Aspects of learning management that are the focus of research are planning, implementing, and assessing learning outcomes. The study was conducted with ethnographic design during five months from July 2023 - November 2023. The main subjects in this study are Chief of Education, tutors, and studenta. Informant as a complement to research data are director of the course and staff. Data collection techniques are carried out by observation, interviews, and document analysis. Test the validity of the data using source triangulation and triangulation techniques. The result of the research shows that the Central Course applies the learning management function well. Learning planning is prepared by chief of education involving tutors, the results of the analysis on lesson plan have met learning planning standards, namely objectives, strategies, teaching materials, media, and learning methods. The learning process is carried out effectively in accordance with the learning objectives delivered by the tutor referring to the lesson plan. To determine learning outcomes of students, assessment is carried out as the final stage of learning. The type of assessment is adjusted to the teaching material in the form of written and non-written. The facilitation of Islamic religious activities held by the Central Course Kediri is well organized in the daily, weekly, and in every Islamic Holiday Commemoration.